2002
DOI: 10.1177/154405910208101208
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Ciprofloxacin and Minocycline by Cultured Human Gingival Fibroblasts

Abstract: Through a mechanism that is unclear, systemic fluoroquinolones and tetracyclines can attain higher levels in gingival fluid than in blood. We hypothesized that gingival fibroblasts take up and accumulate these agents, thereby enhancing their redistribution to the gingiva. Using fluorescence to monitor transport activity, accumulation of fluoroquinolones and tetracyclines was characterized in cultured human gingival fibroblast monolayers. Both were transported in a concentrative, temperature-dependent and satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Gingival fibroblasts possess a transport system that allows them to take up tetracyclines and act as reservoirs for these agents. The transporter exhibits characteristics similar to those of the widely distributed organic cation transporter family, and can move tetracyclines in the forward or reverse direction to maintain equilibrium between intracellular and extracellular concentrations (Yang et al, 2002). Forward transport into fibroblasts presumably occurs when tetracycline levels are increasing or peaking in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gingival fibroblasts possess a transport system that allows them to take up tetracyclines and act as reservoirs for these agents. The transporter exhibits characteristics similar to those of the widely distributed organic cation transporter family, and can move tetracyclines in the forward or reverse direction to maintain equilibrium between intracellular and extracellular concentrations (Yang et al, 2002). Forward transport into fibroblasts presumably occurs when tetracycline levels are increasing or peaking in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…When taken by the systemic route, tetracyclines attain GCF levels that are approximately 4-to 5-fold higher than serum levels (Ciancio et al, 1980;Pascale et al, 1986). Our recent work has shown that gingival fibroblasts express transporters that allow them to take up extracellular tetracyclines and sequester them in the gingiva (Yang et al, 2002). Although the affinity of transport is relatively low, fibroblasts accumulate remarkable amounts of these agents.…”
Section: Introductionmentioning
confidence: 99%
“…We used the pattern of alterations produced by these agents to determine the mechanism of inhibition and the inhibition constant (K i ). We measured intracellular volume by equilibrating fibroblast monolayers with [ 3 H]-water (5 μCi/mL, NEN Life Science Products) exactly as described by Yang et al (2002).…”
Section: Assay Of Naproxen Transportmentioning
confidence: 99%
“…Despite their extensive use, little is known about the factors that govern the distribution of systemic NSAIDs to the tissues of the periodontium. Gingival fibroblasts have been shown to take up tetracyclines and enhance their redistribution from systemic circulation to gingiva (Yang et al, 2002). Fibroblasts are the most prevalent PGE 2 -producing cell in gingival connective tissue and are a logical target for NSAIDs.…”
Section: Introductionmentioning
confidence: 99%
“…One potential explanation for our observation is related to the ability of fluoroquinolones to concentrate intracellularly in human cells (11,22,25). This assumption is confirmed by the higher V of gemifloxacin (Table 1) than of other quinolones.…”
Section: Discussionmentioning
confidence: 54%